Efficacy and safety of mirikizumab (LY3074828) in chronic plaque psoriasis: a systematic review and meta-analysis of randomized controlled trials - Ashraf, Taimoor; Malani, Anand Kumar; Kumar, Dileep; Sagar, Raja Subhash; Raj, Sahil; Kumari, Payal; Kumari, Aanchal; Bajaj, Simran; Basit, Muhammad Abdul; Murad, Muhammad; Kumar, Vikash; Kumar, Ayush (Frontiers in Medicine, 2025)
BackgroundChronic plaque psoriasis is a persistent inflammatory skin condition characterized by erythematous, scaly plaques, significantly impairing the quality of life of affected individuals. Mirikizumab, a humanized monoclonal antibody targeting interleukin-23 (IL-23) p19 subunit, has shown promising efficacy in managing moderate-to-severe cases of this disease. This meta-analysis aims to evaluate the efficacy and safety of mirikizumab in comparison to placebo or other active treatments in this patient population.MethodsA systematic review of randomized controlled trials (RCTs) was conducted. Eligible studies were identified through searches of major databases. The primary endpoint was clinical response measured by Psoriasis Area and Severity Index (PASI) improvement. Safety outcomes were evaluated based on the frequency of events. Data were pooled using a random-effects model to calculate relative risk and mean differences across studies.ResultsMirikizumab significantly increased the rates of achieving PASI 100, PASI 90, and PASI 75 compared to placebo. Mirikizumab also demonstrated superior efficacy in various secondary outcomes compared to placebo. Safety analysis indicated no significant differences in overall treatment-emergent adverse events (TEAEs) or serious adverse events (SAEs), although upper respiratory tract infections occurred more frequently in the mirikizumab group.ConclusionMirikizumab demonstrated a significant improvement in PASI scores compared to placebo and other treatments for chronic plaque psoriasis. Its IL-23 inhibition mechanism suggests a promising therapeutic option with a favorable safety profile. Further research could solidify its position in long-term psoriasis management.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier [CRD42024594843].